Association of altitude and frailty in Chinese older adults: using a cumulative frailty index model - Dong, Yongfei; Ma, Hongmei; Sun, Hao; Li, Yuemei; Li, Xiaofang; Pan, Shiqin; Li, Caixia; Liu, Songbai; Tang, Zaixiang; Li, Lirong (Frontiers in Public Health, 2024)
Objective The population is aging exponentially and the resulting frailty is becoming increasingly evident. We aimed to explore the association between altitude and frailty, and to identify associated factors for frailty. Methods This is a community-based cross-sectional survey. 1,298 participants aged ≥60 years from three different altitudes were included in the study. To quantify frailty, we constructed a frailty index (FI) and a frailty score (FS). The FI was divided into non-frailty, prefrailty, and frailty. The Odds Ratios and confidence intervals (ORs, 95%CIs) were used to evaluate the association between altitude and FI and FS in multivariate ordinal logistic regression and linear regression. Results There were 560 (53.1%) participants in the prefrailty and 488 (37.6%) in the frailty group. The FS increased with higher altitude (P for trend <0.001). Multivariate ordinal logistic regression analysis revealed an association between altitude and frailty, OR = 1.91 (95% CI: 1.38–2.64) in mid-high altitude and 2.49 (95% CI:1.40–4.45) in high altitude. The same trend of association was found in the univariate analysis. The FS increased by 1.69 (95% CI: 0.78–2.60) at mid-high altitude and 3.24 (95%CI:1.66–4.81) at high altitude compared to medium altitude. Conclusion The study indicates that high altitude exposure is an associated factor for frailty in older adults. This association become stronger with higher altitudes. As a result, it is essential to conduct early frailty screening for residents living at high altitudes.